Development and characterization of shape memory ceramics at micro/nanoscale - Zeng, Xiaomei (2017)
Pioneer work has found some signatures of shape memory effect in zirconia based ceramics a few decades ago. However, little work has been carried on since then due to the brittleness and microcracks in the ceramics. This makes it impossible to observe full cycle of shape change and recovery (i.e. shape memory effect). The small magnitude of recoverable strain also limits potential engineering application. Inspired by the work on shape memory alloys, we propose that when the brittle yttria stabilized zirconia (YSZ) are in small volume with high surface area-to-volume ratio, the surface can relieve much of the stress concentrated at grain boundaries, enabling the occurrence martensitic phase transformation and laying a solid foundation for the potential shape memory effect. To prove the hypothesis, we have prepared small volume YSZ ceramics with desired crystal phase, signatures of martensitic transformation were observed without fracture and the hypothesis was proven. However, a large behavior variation was observed in terms of characteristic shape deformation properties like transformation stress and recoverable strain, mainly due to the existence of grain boundaries in YSZ ceramics with nanoscale grains. Our strategy to tackle this challenge was to increase the grain size of the YSZ ceramics to enable single crystal ceramic pillars, by introducing extra dopant of titania. With the introduction of titania, we managed to develop the yttria-titania doped zirconia (YTDZ) ceramics with microscale grains. Characterization of the YTDZ ceramics at grain-scale confirmed the tetragonal phase is present, which is desirable for stress-induced martensitic transformation. The study of martensitic transformation temperatures of YTDZ ceramics guides us to select suitable compositions for potential shape memory effect. The established relationship between martensitic transformation and testing temperatures could be very useful when high temperature applications are desired. The single crystal YTDZ pillars at microscale demonstrated tremendous improvement in fracture strength, enabling robust and reliable shape memory effect, with transformation stress as high as 2.6 GPa and transformation strain of 2.6%. More importantly, the single crystal structure eliminates the effect of grain boundaries, and therefore allows us to quantitatively study the characteristic shape memory properties by decoupling the controlling parameters. A systematic study on the single crystal YTDZ pillars revealed that the featuring shape memory properties are determined by the thermodynamics of stress-induced martensitic transformation. A few controlling parameters such as crystal orientation, testing temperature, ceramic dimension and ceramic composition were explored. Maps for the featuring shape memory properties were constructed over the crystal orientation variation. Such maps suggest that the preferred orientations are different for high martensitic transformation stress, high transformation strain or large energy dissipation. Therefore, depending on the applications, we are able to use ceramics with orientations that maximize the desired properties. In addition to crystal orientation, it was discovered that more doping oxides, larger ceramic dimensions and higher test temperatures all can increase the critical stress for martensitic transformation of zirconia ceramics, and therefore enhance the energy dissipation capacity. The shape memory ceramics made at micro- and nanoscale could have tremendous value for potential applications like sensing, actuation, energy harvesting and conversion, and mechanical damping. The scientific understanding of structure-property relationship may also serve as a possible solution for similar scaling down effect in other systems and as a guide for material selection for various applications in future.